Correlation between length-weight and age in Barbus sharpeyi and Barbus grypus broodstocks in artificial propagation - F. Bosak Kahkesh email ; V. Yavari; F. Amiri; G.H. Makvandi; M. Nikpay (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2011)
This study was carried out to identify proper broodstock of Barbus sharpeyi and Barbus grypus using working fecundity indices. For Barbus sharpeyi three female groups were chosen based on previous experiences that included treatment 1: 650±300g, 1±0.5 years, (T.L) 40.68±2.7cm, treatment 2: 1350±350g, 2.5±0.5 years, (T.L) 47.92±4.63cm and treatment 3: 2200±400g, 4±0.4 years, and (T.L) 59.62±3.56cm. The same male broodstock (700±80g) and 2 year old fish were used for all treatments. For Barbus grypus three female groups were chosen using previous experiences that included treatment 1: 2212.5±780g, 2.5±0.5 years, (T.L) 62.68±6.7cm, treatment 2: 4518±780g, 4±1 years (T.L) 79.12±4.36cm and treatment 3: 7712.5±171g, 7.7±1.3 years and (T.L) 92.62±3.13cm. The same male broodstock (1400±100g) and 2 year old fish were used for all treatments. Female broodstock of the two species were injected 3mg/kg of PG hormone two times at an interval of 10 hours and males were injected 2mg/kg. The maximum working fecundity was seen in treatment 2 for Barbus sharpeyi (33000±1450) and Barbus grypus and (13000.37±4651.57). Functional fecundity were calculated for Barbus sharpeyi in all treatments which was significantly different between treatment 2 and other treatments for the two species. After this stage, the working fecundity was decreased in treatments. We conclude that treatment 2 is the best for selection of broodstocks in the two fish species.